Envelhecimento humano e trabalho: contribuições para a gestão da diversidade - Lima, Tatiane de (My University, 2021)
The findings of an accelerated ageing in the Brazilian population in the last decades, considering the lack of preparation of society in general to meet the demands that arise from this demographic transformation, has turned this issue into a significant social problem. Due to the inversion of the demographic pyramid, society needs to adapt, as Brazil is no longer a country of young people. In 2019, the Social Welfare Reform was approved which requires the social insurance contribution for a longer period of time in order to earn the right to a pension. However, it is known that many people have difficulty in staying longer in the work market. Thus, the goal of this research is to analyze the management?s decisions regarding the older workers in the companies in the region of Serra Gaúcha (the hillside region in the state of Rio Grande do Sul). To that end, a research of exploratory approach with qualitative design was conducted, and the results were analyzed through content analysis according to Bardin. Three managers from three medium-sized companies in Serra Gaúcha were interviewed. As a result, it is important to highlight that three categories were considered, which are: The Intention as To The Policies of People Management; Differentials of The Older Workers; Challenges for The Diversity in The Organizations: Whose Responsibility is It When The Older Ones are Not Hired?. From the analysis of the managers who were interviewed, it was found that that they still observe the age factor in the curriculum of the candidates applying for a job. They mention that the older professionals show a greater commitment to the work and believe that they have distinct behavioral competences when compared to younger ones. On the other hand, they consider that the older ones show less physical strength, less technological familiarity and less adaptation to new techniques and demands. This way, it is possible to understand that the policies may be directed so that there is balance in terms of agility, creativity and modernity, which in general are attributes shown by younger people, while commitment, engagement and a feeling of belonging to the company where they work, which are values usually more present in the older ones. [resumo fornecido pelo autor]
A constatação do acelerado envelhecimento da população brasileira nas últimas décadas, considerando o despreparo da sociedade, em geral, para atender as demandas que surgem com esta transformação demográfica, tornou este tema um problema social significativo. Em virtude da inversão da pirâmide demográfica, a sociedade precisa se adequar, uma vez que o Brasil não é mais um país de jovens. Em 2019, foi aprovada a Reforma da Previdência que exige a contribuição do trabalhador por mais tempo para conquistar o direito à aposentadoria. No entanto, é sabido da dificuldade que muitos encontram para permanecer no mercado de trabalho. Para isso, o objetivo desta pesquisa é analisar as decisões de gestores em relação aos trabalhadores mais velhos em empresas na serra gaúcha. Para tal, realizou-se uma pesquisa de abordagem exploratória com delineamento qualitativo, sendo os resultados analisados por meio análise de conteúdo conforme Bardin. Foram entrevistados três gestores, de três empresas de porte médio da Serra Gaúcha. Como resultado, destaca-se que foram organizadas três categorias, as quais são nomeadas como: Da Intenção a Políticas de Gestão de Pessoas; Diferenciais dos Trabalhadores Mais Velhos; Desafios Para a Diversidade nas Organizações: De Quem é a Responsabilidade da Não Contratação dos Mais Velhos?. A partir da análise das falas dos gestores entrevistados, constatou-se que eles observam ainda, no currículo dos candidatos concorrentes à vaga, o fator da idade. Eles mencionam que profissionais mais velhos apresentam maior comprometimento com o trabalho e acreditam ter competências comportamentais distintas, quando comparados aos jovens. Por outro, consideram que os velhos, apresentam menor força física, maior desconhecimento tecnológicos ou menor adaptação às novas técnicas e demandas. Dessa forma, é possível compreender que as políticas podem ser direcionadas de forma que haja equilíbrio entre agilidade, criatividade e modernidade, atributos em geral apresentados pelos mais jovens, e comprometimento organizacional, engajamento e sentimento de pertença à organização na qual trabalham, valores usualmente mais presentes no público mais velho. [resumo fornecido pelo autor]
Keywords: Envelhecimento; Trabalhadores idosos; Trabalho formal; Integração social; Aging; Older people - Employment; Casual labor; Social integration